Establishing the Nexus Between Iron Status and Markers of Immune Functions Among School Age Children in Ogun State, Nigeria (American Journal of Multidisciplinary Research and Innovation, 2022)
Iron deficiency as a public health problem is based on the seriousness of its consequences on human health suggesting that certain indices of iron status are associated with anthropometric measures which are used independently as markers of immune functions. This study established the relationship between the iron status, and markers of immune functions among school age children in selected Local Government Areas (LGAs) of Ogun state. A multistage sampling technique was used to select three hundred and twelve school age children from the three senatorial districts of Ogun State, Nigeria. A pre-tested and structured questionnaire was used to obtain information on socio-economic characteristics as well as information on Water, Sanitation and Hygiene (WASH) among the respondents. Blood samples of the children were analyzed for biochemical [serum ferritin (SF), C-reactive protein (CRP), Heamoglobin (Hb), reticulocyte count] parameters. Selected immune function markers [CD4, white blood cell differentials (Neutrophils, Lymphocytes, Monocytes, Eosinophils and Basophils)] and parasitic infections (stool examination and Malaria screening) were also measured using standard procedures. Data were analyzed using frequency counts, percentages, means, standard deviations, correlation, T-test and Chi-Square. Results showed that 36.5% of the respondent families earned less than two hundred thousand naira annually. Also, 43.0% and 62.0% of the mothers had secondary and tertiary education respectively. WASH practices showed that 61.1% of the respondents did not have a place for handwashing. The study further revealed that the prevalence of iron deficiency was 23.7%, aneamia was 16.3% while 13.1% of the anaemic children were due to  iron deficiency aneamia with significant sector (p=0.003) and gender (p=0.032) differences. Malaria (17.6%) and helmintes (18.3%) infection also showed a significant difference in the sector (p=0.020, p=0.042). The range of CD4 counts, Neutrophils, Lymphocytes, Monocytes, Basophils and Eosinophils were 708.85 to 727.11, 3.31 to 3.88, 3.03 to 4.38, 0.53 to 0.59, 0.03 to 0.04, 0.33 to 0.38 respectively. CRP positively correlated with household size (r= 0.155), Heamoglobin(r= 0.238), serum ferittin (r= 0.101), and PCV (r= 0.103). CD4 also positively correlated with mothers age and education (r= 0.252; r= 0.142) but negatively related to PCV(r= -0.102) while malaria and Household size (r=0.109) also shows a positive relationship. This study concluded that a significant relationship exists between socio economic status, makers of iron status and infections in the children. Hence, appropriate investigations for iron status and inflammation/infection screening, need to be integral in the evaluation of anaemia, and Interventions that target the multifactorial nature of anaemia in school-aged children need to be strengthened.